A competency-based bachelor’s degree in applied math programming model - Novikienė, Regina (Lietuvos matematikos rinkinys, 2012)
The article aims – to find out what is competence, how to develop those elements must reflect the competency-based training program for the preparation of undergraduate Applied Mathematics.